O patrimônio cultural urbano como construção coletiva: reflexões sobre as possibilidades de ressignificação e atualização do patrimônio cultural na dinâmica urbana contemporânea - Laura Resende Penna de Castro (2020)
The growing urbanization of cities brings relevant impacts to their organization, which, more than the results of formal urban planning, are a reflection of complex and procedural negotiations. We can see that sharing experiences in the construction of public spaces between the institutional power and the various social actors are developing in the big centers, activating spaces long ignored or left aside, thus expanding the possibilities of use and production of these places. These articulations and their transformations challenge the ways our cultural heritage allows us to preserve and use the urban space. Some concepts about cultural heritage, public space and urban reminiscences, as well as temporality and virtuality, appear as reflections that help us to think about heritage in a different perspective from its relevance to contemporary times, allowing society to take ownership of existing structures and resignify. In this sense, some studies are analyzed: Vila Itororó – Canteiro Aberto, in São Paulo, and Luiz Estrela Common Space, in Belo Horizonte, as paradigmatic experiences of making the construction of open and dynamic public spaces effective, shared among multiple social agents. In Belo Horizonte, located in a central-eastern connection region, in a symbolic and structuring area of the city, and the Viaduto Santa Tereza and the Sulacap-SulAmérica Building are other cases presented as potential structures to expand the collective possibilities of creating new uses, reconciling urban dynamics with the permanent updating of its cultural heritage.